The Discourse on Legal Utopia for The People with Disabilities in Order to Remove the Educational Segregation - Abdussamad, Zamroni (Jambura Law Review, 2021)
The right to education for persons with disabilities is still a contemporary legal issue with legal and social problems. The laws and regulations governing the right to education with disabilities are still segregated for the research objectives, namely the Pattern of analyzing the educational arrangements for persons with disabilities and the ideal arrangements for achieving equality in education for persons with disabilities in Indonesia. This research method is categorized into normative legal research types. It is based on the issues and or themes raised as research topics using a philosophical and analytical research approach that is analyzed descriptively. The study results show that the segregated polarization of education for persons with disabilities is contained in Article 10 of Law Number 8 of 2016 concerning Persons with Disabilities and Articles 5, 15 and 32 of Law Number 20 of 2003 concerning the National Education System. The arrangement divides persons with disabilities into particular groups that have an impact on a homogeneous social environment. Therefore, the ideal design is educational equality, as in the United States, where people with disabilities attend regular schools. Besides that, it is necessary to have equal education for people with disabilities in the laws and regulations in Indonesia.